Parapaulipalpina lobata, new species, the first species of Parapaulipalpina Gnaspini, 1996 (Coleoptera: Leiodidae: Cholevinae: Ptomaphagini) from Brazil - Gnaspini, Pedro; Moraes, Gabriella M.; Gomyde, Eduardo C. (Zootaxa, 2024)
Parapaulipalpina lobata Gnaspini, Moraes & Gomyde, new species (Coleoptera: Leiodidae: Cholevinae: Ptomaphagini) is described from Pará State, Northern Brazil. This is the first record of the genus from Brazil. The genus otherwise includes four species described from Northern South America (Colombia, Ecuador, Peru, Venezuela). The apex of the male metatibia of P. lobata sp. nov. is widened and flattened, which is unique in the tribe as a whole, and diagnostic for the species. A key for all known species is provided.